2020
DOI: 10.1111/psyp.13722
|View full text |Cite
|
Sign up to set email alerts
|

The ERP, frequency, and time–frequency correlates of feedback processing: Insights from a large sample study

Abstract: Human learning, at least in part, appears to be dependent on the evaluation of how outcomes of our actions align with our expectations. Over the past 23 years, electroencephalography (EEG) has been used to probe the neural signatures of feedback processing. Seminal work demonstrated a difference in the human event‐related potential (ERP) dependent on whether people were processing correct or incorrect feedback. Since then, these feedback evoked ERPs have been associated with reinforcement learning and conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…One participant was removed due to excessive noise in their EEG data and two others were removed as outliers determined via an evaluation of Cook's distances during analyses (see below). Thus, here we 19 , respectively, to achieve 95% power -confirming our sample size which exceeds these calculations. All participants were recruited through an online sign-up system wherein they earned course credit within psychology courses, were native English speakers, and had normal or corrected-to-normal vision.…”
Section: Participantssupporting
confidence: 82%
“…One participant was removed due to excessive noise in their EEG data and two others were removed as outliers determined via an evaluation of Cook's distances during analyses (see below). Thus, here we 19 , respectively, to achieve 95% power -confirming our sample size which exceeds these calculations. All participants were recruited through an online sign-up system wherein they earned course credit within psychology courses, were native English speakers, and had normal or corrected-to-normal vision.…”
Section: Participantssupporting
confidence: 82%
“…FRN peak latencies were modulated by RPE value, and similar to losses and wins, FRN peak latency was earlier for neutral feedback with negative than positive RPEs. However, Williams et al found an opposite FRN latency shift with wins occurring earlier than losses in a large ( n = 500) gambling dataset using only visual feedback 54 . The latency of FRN and RewP ERPs in our data are also earlier than reported in recent meta-analyses 38 , likely because feedback in our task includes auditory components, which generate faster FRN latencies 33 .…”
Section: Discussionmentioning
confidence: 96%
“…This interpretation is complicated by more recent observations of a P3-like positivity called the Reward Positivity (RewP) that tracks RPE magnitude specifically on positive outcomes (see ref. 46 for review) 47 52 that overlaps in space and delta frequencies with other non-valenced P3 components 53 , 54 . Importantly, this suggests losses and wins generate distinct FRN and RewP ERPs with opposite polarities that interact to some degree depending on their overlap in time and space 48 , 55 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations